Parental Attitudes and Hesitancy About COVID-19 Vaccination Versus Routine Childhood Vaccination in a Selected Hospital in the United Arab Emirates: A Cross-Sectional Study - Vijayalakshmi Selvam MSc; Victoria Funmilayo Hanson PhD; Sneha Pitre PhD (SAGE Publishing, 2024)
Background A complex interplay of social and political influences, cultural and religious beliefs, the availability and interpretation of health and scientific information, individual and population experiences with health systems, and government policies contributes to the anxiety about vaccines and their programs that results in vaccine hesitancy. Vaccine hesitancy is becoming a serious threat to vaccination programs; in 2019, the World Health Organization (WHO) listed it as one of the top ten global health threats. The negative impacts of antivaccination movements are blamed for the major portion of the global resistance to vaccination. Objective To evaluate and compare parental attitudes and reluctance regarding routine childhood vaccinations versus COVID-19 vaccines among children in the United Arab Emirates (UAE). Methods A study of 102 parents with children admitted to SAQR Hospital in Ras Al Khaimah, UAE, was conducted using a convenience sample approach in a descriptive cross-sectional study. One-on-one interviews were conducted to gather data using the standardized Vaccine Hesitancy Scale (VHS) questionnaire developed by the WHO. Statistical Package for Social Sciences version 25 was used for data analysis. Results Vaccine-hesitant respondents are also highly resistant to the required proof of vaccination. A statistically significant difference ( P  = .000) was observed between parental reluctance to receive the COVID-19 vaccination and routine childhood vaccination. Parental knowledge of the COVID-19 vaccine hesitancy ( P  = .001) and confidence ( P  = .000) showed a statistically significant correlation. No significant correlation was observed with sociodemographic factors. Conclusion The impact of vaccine hesitancy on herd immunity, social, psychological, and public health strategies to combat vaccine hesitancy was observed in this study with various challenges to overcome in COVID-19 vaccination campaigns. Expanding access to and acceptance of vaccines among parents in low- and middle-income nations, as well as raising vaccination rates among those who express a lack of confidence in vaccines.